Editorial: Policies, traning processes and tics in higher education - Almeida, Maria de Lourdes Pinto de; Santos Filho, José Camilo dos; Santos, Gildenir Carolino (Universidade Estadual de Campinas, 2018)
We are radiant with the closing of another edition that completes the 2018 collection (volume 4, number 3, set./dez.), Having proven that the adoption of bilingualism in the magazine worked very well as a new methodology of 2018. We have practically 100 % of work in English and Portuguese. The theme of this last edition of 2018 talks about "Policies, training processes and TICS in higher education".